(untitled) (Modern education and development, 2025)
This article examines the essential role of teachers’ professional competence and flexible pedagogical approaches in the successful implementation of inclusive education. It highlights the necessity for educators to possess not only subject knowledge but also adaptive strategies, emotional intelligence, and a deep understanding of individual student needs. The study explores how inclusive education expands the boundaries of traditional teaching, requiring continuous professional development, differentiated instruction, and collaboration with parents and specialists. The article also provides practical recommendations for supporting diverse learners in inclusive classrooms and emphasizes the importance of creating an equitable and supportive learning environment for all students.